Pengaruh Faktor Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Toko Automart Jakarta Pusat - Edwin Sholeh Rahmanullah; Dian Pangastuti; Teguh Santoso (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.In the world of automotive retail business, competition between stores is getting tighter, especiallycar accessories shopping centers, which is currently followed by the emergence of modern caraccessories shopping centers in shopping centers located in Central Jakarta in the last 5 years.Customers have a wide choice of stores offering a variety of automotive products at varying pricesand quality, as well as a variety of services. Automart Store sales over a period of 5 years havestarted to increase from previously being stable in the middle of the Automart Store sales data flowchart. In an effort to maintain customer loyalty, stores like Automart need to pay serious attention toseveral key factors that influence customer satisfaction, namely price, product quality and servicequality. The variables studied consist of three independent variables, namely price, product qualityand service quality, as well as one dependent variable, namely customer satisfaction. The method 448|Jurnal Administrasi Bisnis Vol 5 No 5 Oktober 2025 used in this research is to use a quantitative method to process data obtained from the research location in the form of numbers. The data collection method uses a questionnaire by distributingquestionnaires to customers of the Jakarta Automart Store who have shopped and the data obtainedfrom this study are as many as 140 customers of the Jakarta Automart Store who came to shop.Data collection techniques using Validity and Reliability Tests. Data analysis test using multiple linearregression. Hypothesis testing techniques use partial tests and simultaneous tests. The results of thestudy show that price, product quality and service factors simultaneously have a significant influenceon customer satisfaction. This shows that simultaneously the magnitude of the Price Factor, ProductQuality and Service Quality on Customer Satisfaction is 0.480 or 48.0%. Meanwhile, the remaining52.0% is determined by other variables. Keywords: Compensastion, Work Enviroment, Employee Morale